Analisis Perbaikan Tanah Lunak dengan Kombinasi Preloading dan Prefabricated Vertical Drain pada Pembangunan Jalan Tol Pematang Panggang – Kayu Agung, Sumatera Selatan - Paksitya Purnama Putra; Eka Patriyandi Oktavian; Wiwik Yunarni Widiarti (Universitas Jember, 2021)
The construction project of Pematang Panggang - Kayu Agung Toll Road, Section 4 is located in Ogan Komering Ilir Regency, South Sumatra. This project area has a soft clay soil type. With the condition of the soft soil, soft soil repairs need to be done at the project site. The soil improvement used is the Preloading Method combination of Prefabricated Vertical Drain (PVD) and Prefabricated Horizontal Drain (PHD). This method of repair is done by comparing the time of soil consolidation before and after using the Preloading combination of Prefabricated Vertical Drain (PVD) and Prefabricated Horizontal Drain (PHD) by measuring the time needed to achieve consolidation of 90% and the effectiveness of the Prefabricated Vertical Drain (PVD) installation pattern. With the installation of Prefabricated Vertical Drain on the pattern of installation of rectangles / rectangles with a distance of 0.8 m, it can accelerate consolidation to 19 weeks from the time before PVD is installed. It takes 130 years. Then hoarding with Hinisial = 11 meters is carried out, for the first stage of hoarding with a value of Hcr = 4.375 m carried out up to 4 m, the decrease that occurs is 1.0735 m so that the remaining stock is 2.9265 m. After the value of Cu (Undrained cohesion) has increased, for the second stage of stockpiling, the value of Hcr = 13,526 m. The decrease that occurred in the second stage was 1.6634 m with the rest of the embankment 5.3366 m. So the total embankment height that has been compressed is 8.2631 m. and to reach the Hfinal the next hoarding stage is carried out to reach 8.69 m